2011
DOI: 10.1540/jsmr.47.67
|View full text |Cite
|
Sign up to set email alerts
|

SM2+/- male mice are predisposed to develop urinary tract obstruction and hyper contractility of the bladder smooth muscle upon ageing

Abstract: We previously showed that complete loss of smooth muscle myosin heavy chain isoform 2 (SM2) resulted in postnatal lethality, but in het mice a partial loss of SM2 (SM2 +/-) was accompanied by down-regulation of SM1 with unaltered SM2:SM1 ratio. To determine whether a normal bladder function would be maintained throughout its lifespan, we aged WT and SM2 +/-mice up to 18 months and analyzed a) SM2:SM1 ratio b) bladder smooth muscle structure and c) function in SM2 +/-het mice. A notable finding was that ~50% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Results are also conflicting regarding a role of carboxyl terminal isoforms on filament assembly (29;30;57). A recent study using SM2 knockout mice shows SM (+/−) male mice with relatively high ratio of SM1/SM2 are predisposed to develop urinary tract obstruction and hypercontractility of bladder smooth muscle upon aging (56). Thus, there is evidence that suggests a relationship between changes in MHC isoform expression and smooth muscle function in this study.…”
Section: Discussionsupporting
confidence: 56%
“…Results are also conflicting regarding a role of carboxyl terminal isoforms on filament assembly (29;30;57). A recent study using SM2 knockout mice shows SM (+/−) male mice with relatively high ratio of SM1/SM2 are predisposed to develop urinary tract obstruction and hypercontractility of bladder smooth muscle upon aging (56). Thus, there is evidence that suggests a relationship between changes in MHC isoform expression and smooth muscle function in this study.…”
Section: Discussionsupporting
confidence: 56%
“…Results are also conflicting regarding a role of carboxyl-terminal isoforms on filament assembly [29,30,59]. A recent study using SM2 knockout mice shows SM (+/-) male mice with relatively high ratio of SM1/SM2 are predisposed to develop urinary tract obstruction and hypercontractility of bladder smooth muscle upon aging [58]. Thus, there is evidence that suggests a relationship between changes in MHC isoform expression and smooth muscle function in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Alterations in smooth muscle carboxyl‐terminal isoform expression have also been reported in animal models of bladder outlet obstruction , diabetes , atherosclerosis , and hypertension . Despite reports of changes in carboxyl‐terminal isoform expression in both physiological and pathological conditions, the physiological relevance of the relative expression of SM1/SM2 isoforms is unresolved . Some , but not all , studies have demonstrated a positive correlation between the SM1 isoform and unloaded shortening velocity.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, mice that have reduced levels of smooth muscle myosin isoforms SM1 and SM2 (SM2 +/- mice) exhibit a bladder phenotype that is strikingly similar to that of Mras -/- mice. About half of SM2 +/- males exhibit bladder distension at 18 months of age, and the detrusor is hypersensitive to both K + depolarization and carbachol stimulation [ 61 ]. Thus, it is tempting to speculate that M-Ras might dampen smooth muscle contractility by negatively affecting smooth muscle actin (SMA) polymerization.…”
Section: Discussionmentioning
confidence: 99%